Cardiac Involvement in Eosinophilic Granulomatosis With Polyangiitis: A Retrospective Study in the Chinese Population - Chen, Yingying; Guo, Xiaoxiao; Zhou, Jiaxin; Li, Jing; Wu, Qingjun; Yang, Hongxian; Zhang, Shangzhu; Fei, Yunyun; Zhang, Wen; Zhao, Yan; Zhang, Fengchun; Zeng, Xiaofeng (Frontiers in Medicine, 2020)
Introduction: Cardiac involvement in eosinophilic granulomatosis with polyangiitis (EGPA) is associated with a poor prognosis and high mortality; however, few studies about cardiac involvement in EGPA in the Chinese population are available. We conducted this study to determine the clinical characteristics and overall outcomes of Chinese EGPA patients with cardiac involvement. Materials and Methods: We retrospectively collected the clinical data of 83 patients diagnosed with EGPA and analyzed the differences between the patients with and without cardiac involvement. Results: The prevalence of cardiac involvement in EGPA in this cohort was 27.7%. Compared with those without cardiac involvement, EGPA patients with cardiac involvement tended to have a younger age at onset (mean ± SD: 38.4 ± 10.5 vs. 42.1 ± 15.9 years, respectively, p = 0.039), higher eosinophil count (median [IQR]: 5810 [4020–11090] vs. 2880 [1530–6570] n/μL, respectively, p = 0.004), higher disease activity assessed using the Birmingham vasculitis activity score (BVAS) (median [IQR]: 20 [16–28] vs. 15 [12–18], respectively, p = 0.001), and poorer prognosis (Five Factor Score [FFS] ≥ 1: 100% vs. 38.3%, respectively, p = 0.001). In the cardiac involvement group, 43.5% of patients were asymptomatic, but cardiac abnormalities could be detected by cardiac examinations. With appropriate treatment, the overall outcomes of EGPA patients with cardiac involvement in our cohort were good, with only 3 (13%) patients dying in the acute phase and no patients dying during follow-up. Conclusions: Cardiac involvement in EGPA was associated with a younger age at onset, higher eosinophil count, higher disease activity, and a poorer prognosis. Comprehensive cardiac examinations and appropriate treatment are essential to improve the prognosis of those with cardiac involvement.